2004
DOI: 10.1080/0022293031000155386
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the subterranean amphipod genus Bahadzia (Hadziidae), with description of a new species, redescription of B. yagerae, and analysis of phylogeny and biogeography

Abstract: Bahadzia caymanensis, a new stygobitic species is described from a shallow, weakly brackish-water pool in a small cave on Grand Cayman Island in the Cayman Islands. Further exploration and collecting from the type-locality of Bahadzia yagerae in Cuba has provided more data, allowing for a thorough redescription of this species. With the description of Bahadzia caymanensis, there are now 11 species within the genus. Revised phylogenetic and biogeographic analyses of Bahadzia offer further support for a close ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Cladistic analysis performed including Bahadzia , the third stygobiont hadziid genus known from the peninsula and another 13 further hadziid genera suggested that Mayaweckelia and Tuluweckelia are sister genera to Bahadzia and may even be derived from a Bahadzia -like ancestor (Holsinger 1992, Sawicki and Holsinger 2004). Our mitochondrial sequence analysis supports this idea, though, it would be necessary to collect individuals of both Yucatán Bahadzia species ( B. bozanici and B. setodactylus ) to further solve this question.…”
Section: Discussionmentioning
confidence: 99%
“…Cladistic analysis performed including Bahadzia , the third stygobiont hadziid genus known from the peninsula and another 13 further hadziid genera suggested that Mayaweckelia and Tuluweckelia are sister genera to Bahadzia and may even be derived from a Bahadzia -like ancestor (Holsinger 1992, Sawicki and Holsinger 2004). Our mitochondrial sequence analysis supports this idea, though, it would be necessary to collect individuals of both Yucatán Bahadzia species ( B. bozanici and B. setodactylus ) to further solve this question.…”
Section: Discussionmentioning
confidence: 99%
“…As the years went on, his interest in subterranean amphipods became global, and he described dozens of new species from throughout the world. These included species of Crangonyx and Stygobromus from outside North America (42,123,130), and the cave and interstitial species in the families Bogidiellidae (89,90,91,108,111,113) and Hadziidae (27,53,57,61,74,78,79,87,97,99,100,102,105). His enthusiasm for the morphology of cave amphipods was boundless.…”
mentioning
confidence: 99%